Associations between ovarian hormones and emotional eating across the menstrual cycle: Do ovulatory shifts in hormones matter?. Issue 2 (15th January 2019) - Fowler, Natasha; Keel, Pamela K.; Burt, S. Alexandra; Neale, Michael; Boker, Steven; Sisk, Cheryl L.; Klump, Kelly L.
Abstract: Objective: Elevated ovarian hormone levels are associated with increased risk for binge eating (BE) and emotional eating (EE) during the midluteal phase of the menstrual cycle. However, past studies have not examined whether pronounced hormonal changes that precede the midluteal phase (i.e., the dramatic decrease in estradiol and increase in progesterone during/after ovulation) also influence midluteal increases in binge‐related symptoms. Past theories and studies of phenotypes strongly related to BE (e.g., depression) suggest that these pronounced hormonal changes may also contribute. This study examined this possibility in 375 female twins (aged 15–25 years) from the Michigan State University Twin Registry. Methods: Daily ratings of EE (assessed with the Dutch Eating Behavior Questionnaire) and daily saliva samples of estradiol and progesterone were collected for 45 consecutive days. Results: No significant associations were found between pronounced changes in estradiol or progesterone across ovulation and changes in EE scores in the midluteal phase. Results remained unchanged after controlling for body mass index and negative affect and examining participants with clinical BE episodes or more extreme hormonal fluctuations. Discussion: In aggregate, the current findings and past data suggest that hormone levels are more significant predictors of EE than pronounced hormonal changes across the menstrual cycle.